RELASI KOMPETENSI BIROKRAT DAN KAPASITAS KELEMBAGAAN BIROKRASI TERHADAP POLA KEBIJAKAN PARIWISATA DI KOTA PALEMBANG (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2014)
This article aims to explain the relation of bureaucrats competency and institutional capacity of bureaucracy to the pattern of tourism policy in Palembang. Based on empirical research using qualitative approaches-positivist, researcher concluded that (a) the capacity of bureaucrats and bureaucracy, especially Department of Tourism and Culture in Palembang City, in managing tourism affairs is still weak; (b) there is a causal relationship between bureaucrats competency with institutional capacity competency, as well as the contribution of bureaucrats competency and institutional capacity compentency on the pattern of policies and programs of Department of Tourism and Culture in Palembang City simultaneously. Based on these findings, the authors suggested that Palembang municipality government should managing bureaucrats and institutional competency as a starting point of tourism development reform of in their city.